Identification of Seawater Quality Around PLTU Teluk Sepang Outlet Based on Oceanographic Parameters - Gerry, Muamar; Silaban, Angeli; Johan, Septi; Lidiawati, Liza (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2025)
The heat waste produced by the PLTU is released directly into the ocean, significantly impacting the quality of sea water. This research intends to assess the quality of sea water near the PLTU Teluk Sepang outlet in Bengkulu City using oceanographic parameters. Data collection was conducted in the field at eight sites that represent the area around the PLTU outlet, focusing on parameters such as sea water temperature, salinity, density, pH, and ocean currents. The obtained measurement results were then compared against the standards set by KepMenLH No. 51, 2004. The findings reveal that parameters such as temperature, pH, and salinity did not meet the quality standards necessary for marine biota ecosystems; the average temperature ranges from 33.58 to 35.39 °C, the pH levels were between 8.59 and 8.76, indicating an alkaline condition, and salinity measures between 24.7 and 26.9 ‰, all of which fall below the standards established by KepMenLH No. 51, 2004. This research demonstrates that the discharge of heat waste substantially pollutes the sea water quality around the PLTU Teluk Sepang outlet in Bengkulu City, particularly affecting sea water temperature, which significantly influences the metabolism of marine biota.